1996
DOI: 10.1021/ic9606441
|View full text |Cite
|
Sign up to set email alerts
|

Model for the Reduced Schiff Base Intermediate between Amino Acids and Pyridoxal:  Copper(II) Complexes of N-(2-Hydroxybenzyl)amino Acids with Nonpolar Side Chains and the Crystal Structures of [Cu(N-(2-hydroxybenzyl)-d,l-alanine)(phen)]·H2O and [Cu(N-(2-hydroxybenzyl)-d,l-alanine)(imidazole)]

Abstract: Copper(II) complexes with reduced Schiff base ligands of amino acids possessing nonpolar side chains with salicylaldehyde have been synthesized. Ternary complexes with imidazole, 1,10-phenanthroline, and pyridine have been prepared and characterized for N-(2-hydroxybenzyl)-D,L-alanine. The crystal structures of [(N-(2-hydroxybenzyl)-D,L-alanine)(1,10-phenanthroline)Cu(II)] monohydrate ([Cu(SAla)phen].H(2)O) and [(N-(2-hydroxybenzyl)-D,L-alanine)(imidazole)Cu(II)] ([Cu(SAla)Him]), have been determined. [Cu(SAla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 35 publications
4
83
1
3
Order By: Relevance
“…The ethyl ester H 2 EtL1 was produced in a reaction sequence (Scheme 1) involving a statistical reaction between N-(2-pyridylmethyl)glycine ethyl ester, 36 …”
Section: Synthesis Of the Ligand And Complexmentioning
confidence: 99%
“…The ethyl ester H 2 EtL1 was produced in a reaction sequence (Scheme 1) involving a statistical reaction between N-(2-pyridylmethyl)glycine ethyl ester, 36 …”
Section: Synthesis Of the Ligand And Complexmentioning
confidence: 99%
“…intermolecular N-H···O hydrogen bond between the NH 2 and sulfonate groups in the solid state and in solution has been utilized as a crystal engineering tool. [12] The properties and the functions of the N-H···O hydrogen bonds involving coordinated -SO 3 -groups in a dinuclear calcium complex have been reported. [24] As in 1, medium strong C-H···O hydrogen bonds have also been observed in the solid state.…”
Section: Crystal Structure Of [Cu 2 (Sae) 2 ]·2h 2 O (4)mentioning
confidence: 99%
“…Several copper complexes of reduced Schiff-base ligands formed between salicylaldehyde and amino acids were explored to serve as models for the intermediate species in biological racemization and transamination reactions. [3] Making use of these advantages, we employed such reduced Schiff-base ligands to synthesize dinuclear Cu II and Zn II complexes that exhibit interesting structural transformations in the solid state. [4] Further, in our recent report, we showed that incorporation of an additional carboxylate group in the side arm of the ligand N-(2-hydroxybenzyl)--glutamic acid formed between salicylaldehyde and -glutamic acid resulted in a novel structural display of a spiral staircase conformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since pseudo-square-planar monoligand chelates of tridentate Schiff bases derived from salicylic aldehyde and 1,2-amino alcohols 10 [11] or a-amino acids 11 [12] can be used as catalysts, we concluded that the metal center either has two free coordination sites in cis position or that theseÐas in the case of the tetrahedral complexesÐcan be readily created. Thus we assume the crucial step in the reaction to be the nucleophilic attack of the hydroxylic component at a copper bisketene complex that has a structure analogous to that described for a cobalt 1,2-bisketene chelate.…”
Section: In Memoriam Horst Pracejusmentioning
confidence: 95%